Numerical simulations of multi-phase electro-hydrodynamics flows using a simple incompressible smoothed particle hydrodynamics method. (1st January 2021) - Almasi, F.; Shadloo, M.S.; Hadjadj, A.; Ozbulut, M.; Tofighi, N.; Yildiz, M.
Abstract: Practically, every processing technology deals with complex multi-phase flows and predicting the fluid flow behavior is crucial for these processes. Current study discusses the application of a mesh-less numerical methodology, i.e. Incompressible Smoothed Particle Hydrodynamics (ISPH) to investigate the behavior of different multi-phase flow systems. This work is presented in a coherent way with increasing test problem difficulties and their concerned physical complexities. A wide range of problems including Laplace's law, bubble rising, bubble suspension under an external electric field are considered for a code validation purpose, while the numerical results manifest very good accordance with the experimental and theoretical data. Finally, we show the effectiveness of using an external electric field for controlling a complex problem such as Couette flow for a range of electrical permittivity and electrical conductivity ratios. It is noted that the Electrohydrodynamics (EHD) effect on a suspended droplet in Couette flow case is simulated for the first time using the SPH method.